The Mind of a Poet The Prelude, Commentary / Volume Two The Prelude, A Commentary / The Prelude, A Commentary / Volume Two - Havens, Raymond Dexter, 1880-1954.; Project Muse.; Project Muse. (2019)
This book seeks to study the mind of a poet, specifically by picking William Wordsworth as a case study. The reason for signaling out Wordsworth as the person in whom to study the mind of a poet is that The Prelude reveals with unusual fullness a mind that is fundamentally poetic. Even its peculiarities, its numerous limitations, and its unusual emphases are in the main those of a poet. Besides, poetry - not, as with many other writers, religious or social problems, humanitarianism, science, politics, economics, metaphysics, or literary criticism -was the chief concern of his creative years. Further, the sheer amount of verse, criticism, letters, and journals Wordsworth produced makes him an excellent choice for a study of this kind. from the publisher
Originally published as Johns Hopkins Press in 1941, fourth printing 1967.
The text of this book is licensed under a Creative Commons Attribution-NonCommercial-No Derivatives 4.0 International License
Open access edition supported by the National Endowment for the Humanities / Andrew W. Mellon Foundation Humanities Open Book Program.
Includes bibliographic references and index.
Description based on print version record.
Keywords: Wordsworth, William, -- 1770-1850.; Wordsworth, William, -- 1770-1850.; Wordsworth, William, -- 1770-1850.; Wordsworth, William, -- 1770-1850.; Prelude (Wordsworth, William); Electronic books; Electronic books